Overview on attention deficit hyperactivity disorder among children from Delta regions of Egypt (a 10 years-study) - Al-Haggar, Mohammad; El-Baz, Rizk; Youseff, Hisham; Othman, Nierra; Ali, Rabab (Journal of Pediatric Neurology, 2006)
As inattention and hyperactivity are highly prevalent among school children, we aimed to introduce an overview on ADHD (attention deficit hyperactivity disorder) in Delta regions of Egypt, to evaluate its diagnostic accuracy, and to suggest a de novo method for diagnosis among Egyptian school children. This retrospective epidemiological study was conducted on cases registered in database files of Pediatrics Genetics unit, in Mansoura University Children’s Hospital, which serves all Delta regions of Egypt. Initial diagnosis of 356 registered cases was based upon detailed history, signs and symptoms without applying any strict criteria. Some cases were receiving stimulants drugs however almost all were under behavioral therapy. All cases were currently re-evaluated applying DSM-IV criteria (Diagnostic and Statistical Manual of Mental disorders, 4th edition) and Conners’ Developmental approach. Diagnosis of ADHD was confirmed in 283 children excluding 73 cases (20.5%); they were 211 boys and 72 girls (boys/girls ratio 3/1), age range 7–12 years (mean 9.5 ± 3.13 years). Most cases whether at initial registration or during final assessment were associated with hyperactivity/impulsivity however predominantly inattentive cases constituted 39.04%. Half of excluded cases were predominantly inattentive (49.3%) and 61.7% of exclusion were due to clinical improvements. Other exclusionary causes included sleep disorders, hyperthyroidism, communication disorders, mental retardation and autism. Positive family history was reported in 49.8% mostly among inattentive and combined types. ADHD is not uncommon in our community; its frequency among cases referred for childhood diagnostic clinics approximates 79.5%, and prevalence would be much lower if evaluated among asymptomatic school children. Inattentive ADHD is frequently overlooked and its response to therapy is usually satisfactory.
Keywords: Attention deficit; hyperactivity; epidemiology; Egypt